The Relationship between Parenting Style and Learning Motivation on the Science Learning Outcomes of Grade IV Students - Bela Santuni; I Ketut Gading; I Kadek Edi Yudiana (Universitas Pendidikan Ganesha, 2025)
Lack of attention and support from parents and low student motivation are factors that affect learning outcomes. Proper parenting creates a supportive learning environment, while high learning motivation encourages students to put more effort into understanding the material. This study aims to determine the relationship between parenting and learning motivation on IPAS learning outcomes of Grade IV students. This study used the ex post facto correlational method with data collection techniques in the form of questionnaires and recording students' IPAS scores. The research sample consisted of 101 students selected using stratified proportional random sampling technique. Data analysis was done using multiple regression techniques. The results showed: there is a significant relationship between parenting patterns and IPAS learning outcomes, there is a significant relationship between learning motivation and IPAS learning outcomes, and simultaneously there is a significant relationship between parenting patterns and learning motivation on IPAS learning outcomes. The results showed that parenting and learning motivation have a significant relationship with student learning outcomes. In order to achieve optimal learning outcomes, students need to have a balanced parenting style and high learning motivation.